Simulation of a-Si PV system linked to the grid by DC-DC boost and two-level converter - Melicio, Rui (2015)
This paper is about a PV system linked to the electric grid by power electronic converters. The modeling for the converters emulates the association of a DC-DC boost with a twolevel power inverter in order to follow the performance of a testing commercial inverter employed on an experimental system. It is used pulse width modulation by sliding mode control associated with space vector modulation for control the boost and the inverter. The PV system is described by the five parameters equivalent circuit and parameter identification is carried out. Maximum power point tracking is implemented by a dP/dV procedure. Simulation studies are performed and a comparison with the testing experimental system is presented.